Engineering of fully humanized and vascularized 3D bone marrow niches sustaining undifferentiated human cord blood hematopoietic stem and progenitor cells. (September 2021) - Born, Gordian; Nikolova, Marina; Scherberich, Arnaud; Treutlein, Barbara; García-García, Andrés; Martin, Ivan
Hematopoietic stem and progenitor cells (HSPCs) are frequently located around the bone marrow (BM) vasculature. These so-called perivascular niches regulate HSC function both in health and disease, but they have been poorly studied in humans due to the scarcity of models integrating complete human vascular structures. Herein, we propose the stromal vascular fraction (SVF) derived from human adipose tissue as a cell source to vascularize 3D osteoblastic BM niches engineered in perfusion bioreactors. We show that SVF cells form self-assembled capillary structures, composed by endothelial and perivascular cells, that add to the osteogenic matrix secreted by BM mesenchymal stromal cells in these engineered niches. In comparison to avascular osteoblastic niches, vascularized BM niches better maintain immunophenotypically-defined cord blood (CB) HSCs without affecting cell proliferation. In contrast, HSPCs cultured in vascularized BM niches showed increased CFU-granulocyte-erythrocyte-monocyte-megakaryocyte (CFU-GEMM) numbers. The vascularization also contributed to better preserve osteogenic gene expression in the niche, demonstrating that niche vascularization has an influence on both hematopoietic and stromal compartments. In summary, we have engineered a fully humanized and vascularized 3D BM tissue to model native human endosteal perivascular niches and revealed functional implications of this vascularization in sustaining undifferentiated CB HSPCs. This system provides a unique modular platform to explore hemato-vascular interactions in human healthy/pathological hematopoiesis.